HUBUNGAN PERSEPSI SISWA TENTANG PENGGUNAAN STRATEGI PEMBELAJARAN DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH DI MA DARUL HUDA PUSAT MANDALAWANGI PANDEGLANG - mohammadnasrudin (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2021)
The Relationship of Students' Perceptions About the Use of Learning Strategies and Motivation Learning with Student Learning Outcomes in Fiqh Subjects at MA Darul Huda Center Mandalawangi Pandeglang. Student Perceptions About Using Strategy Learning and Learning Motivation is very important in learning because it has a significant relationship to the results study fiqh at Madrasah Aliyah Darul Huda, Mandalawangi Center, Pandeglang. ByTherefore, to get good learning outcomes, students' perceptions are expected to be positiveon the learning, strategies implemented by the teacher, and motivating students to implement. The purpose of this research is to analyze and test the hypothesis regarding the relationship between students' perceptions of the use of strategies learning and learning motivation with Fiqh learning outcomes. As for the benefits of This research provides a treasure trove of knowledge about students' perceptions of the use of learning strategies and learning motivation related to the results of student learning. the method used in this research is the descriptive method with the correlation technique. The population of this study was all Madrasah students Aliyah Darul Huda Center Mandalawangi Pandeglang even semester of the school year 2019-2020 which recorded 281 students. The sample consists of all class XI, namely 81 students. The sampling technique used is purposive sampling. Analysis data using multiple correlation tests and multiple regression tests. The conclusion obtained from the results of this study are: There is a positive and significant relationship between X1 and Y of 0.936, meaning that it is classified as very strong, there is a relationship which is positive and significant between X2 and Y of 0.479, meaning that it is quite strong, There is a positive and significant relationship between X1, X2, and Y of 0.95, which means it is classified as very strong. Thus, the results of this study are useful for improving learning outcomes through students' perceptions of the use of strategies learning and learning motivation.